The Natural History and Predictors for Intervention in Patients with Small Renal Mass Undergoing Active Surveillance - Zaher Bahouth; Sarel Halachmi; Gil Meyer; Ofir Avitan; Boaz Moskovitz; Ofer Nativ (Advances in Urology)
Aim. To describe the natural history of small renal mass on active surveillance and identify parameters that could help in predicting the need for intervention in patients with small renal masses undergoing active surveillance. We also discuss the need for renal biopsy in the management of these patients. Methods. A retrospective analysis of 78 renal masses ≤4 cm diagnosed at our Urology Department at Bnai Zion Medical Center between September 2003 and March 2012. Results. Seventy patients with 78 small renal masses were analyzed. The mean age at diagnosis was 68 years (47–89). The mean follow-up period was 34 months (12–112). In 54 of 78 masses there was a growth of at least 2 mm between imaging on last available follow-up and diagnosis. Eight of the 54 (15%) masses which grew in size underwent a nephron-sparing surgery, of which two were oncocytomas and six were renal cell carcinoma. Growth rate and mass diameter on diagnosis were significantly greater in the group of patients who underwent a surgery. Conclusions. Small renal masses might eventually be managed by active surveillance without compromising survival or surgical approach. All masses that were eventually excised underwent a nephron-sparing surgery. None of the patients developed metastases.